A new species of the genus Glischrochilus Reitter (Coleoptera: Nitidulidae: Cryptarchinae) from China - Lasoń, Andrzej; Mazur, Miłosz A. (Zootaxa, 2016)
The cosmopolitan genus Glischrochilus Reitter, 1873 (Nitidulidae: Cryptarchinae) is distributed in Holarctic and Oriental regions. According to the most recent catalogue (Jelínek & Audisio 2007), 32 species are known from the Palaearctic region. In China the genus is represented by 13 species, most of which were described by Jelínek (1975, 1982, 1999) and Lasoń (2009).